2020
DOI: 10.4103/ijpc.ijpc_228_19
|View full text |Cite
|
Sign up to set email alerts
|

The concept of do not resuscitate for the families of the patients at king abdul-aziz university hospital

Abstract: Aim: Do not resuscitate (DNR) is an order in medical practice for the patients who are suffering from a grave medical condition, and their life is in danger to end. DNR decision-making varies from one hospital to another. This study is aimed to assess the knowledge of the patients' relatives about DNR concept and their opinion about the DNR decision-making. Materials and Methods: This was a nonintervention cross-sectional study conducted, during 2016, among 420 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These findings are like the findings of Vranick et al (2022), who suggested that every facility with palliative care facility should have a DNR policy in place. This data also supports the extensive evidence that there needs to be more understanding of the DNR concept (Alsaati et al, 2020).…”
Section: Lack Of Awareness and Misunderstanding Of Dnr Orderssupporting
confidence: 84%
“…These findings are like the findings of Vranick et al (2022), who suggested that every facility with palliative care facility should have a DNR policy in place. This data also supports the extensive evidence that there needs to be more understanding of the DNR concept (Alsaati et al, 2020).…”
Section: Lack Of Awareness and Misunderstanding Of Dnr Orderssupporting
confidence: 84%
“…It is acknowledged that there is a need to make DNACPR decisions, as soon as possible in a patient's admission, 18 as part of a timely process 19 and for this to be commenced as early as possible after a diagnosis of an incurable disease. 20 There is a lack of clarity as to when the right time is for decisions to be made within the admission-to-discharge journey. Discussions were held in the emergency department, 21 admission period, 22 23 after admission, 24 within 48 hours of admission, 25 within 72 hours of admission 26 or following admission secondary to their life-limiting illness.…”
Section: Timing Of Decision-makingmentioning
confidence: 99%
“…In addition to providing information to the patient, Alsaati et al, 20 Alwazzeh et al 64 and Ding et al 69 recommend that healthcare professionals also provide an explanation of DNACPR decisions to those close to the patient. This can help avoid misunderstandings, avoid stress on those close to the patient and create a better atmosphere for communication.…”
Section: Recommendations From the Literaturementioning
confidence: 99%